Recommendations for the diagnosis of respiratory syncytial virus (RSV) infection in children. The Polish Society of Paediatrics and the National Paediatric Consultant’s recommendations - Wrotek, August; Jackowska, Teresa; Mazur, Artur; Szczepański, Tomasz; Toporowska-Kowalska, Ewa; Dembiński, Łukasz; Beń-Skowronek, Iwona; Medyńska, Anna; Plata-Nazar, Katarzyna; Styczyński, Jan; Hartmann, Piotr; Jarmoliński, Tomasz; et al. (Pediatria Polska - Polish Journal of Paediatrics, 2025)
Respiratory syncytial virus (RSV) is one of the most important aetiological factors in acute respiratory tractinfections, and the availability of diagnostic methods, including rapid antigen tests (RADTs) and molecularbased assays, is increasing in Poland. The Polish Society of Paediatrics presents these recommendations in order to unify the clinical approach to RSV testing and clarify confusion related to testing. We hereby providecca comprehensive overview of general characteristics of the test methods, recommendations for interpretation of test results and practical implications of the results. We also indicate the goals of RSV testing and recommendations for selected clinical diagnoses. The aim of the guidelines is to maximise the use of available tests in both inpatient and outpatient settings and to assist paediatricians in making clinical decisions.